Employee value proposition as the core of HR branding: a strategy of trust, authenticity and talent development - Ilich, Liudmyla (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2025)
Introduction. The object of the study is the HR branding system of modern organizations, which reflects the interrelation between the Employee Value Proposition (EVP), corporate culture, and managerial practices for personnel development. HR branding is viewed as a multidimensional phenomenon that integrates marketing, psychological, and social components, fostering trust, loyalty, and employee engagement. Its key characteristics include authenticity, strategic orientation, human-centeredness, and alignment with business objectives.Problem statement. In the modern context of intense competition for talent, business digitalization, and the growing importance of employee engagement, HR branding is transforming from a marketing tool into a strategic system of human capital management. At the core of this system lies the Employee Value Proposition (EVP), which builds trust, loyalty, and a culture of shared responsibility between the company and its people.Unresolved aspects of the problem. Despite the growing interest in HR branding, the role of an authentic EVP as a driver of organizational competitiveness and its integration into managerial practices remain insufficiently explored.Purpose of the article. The purpose of the study is to theoretically substantiate the Employee Value Proposition (EVP) as the strategic core of a modern organization’s HR brand and to identify its key dimensions that ensure trust, authenticity, and talent development.Presentation of the main material. Based on an interdisciplinary approach combining the concepts of management, marketing, and organizational behavior, the study systematizes scientific approaches to HR branding and identifies its main components: EVP, corporate culture, employee experience, reputation, innovation, and corporate social responsibility. The analysis of international and Ukrainian research (2020 – 2025) demonstrates that an effective EVP integrates mission, values, employee experience, and social responsibility into a unified system of mutual commitments. Five key dimensions of modern EVP are highlighted: meaningful work and mission, professional growth, supportive corporate culture, flexibility and work-life balance, and social responsibility.Conclusions. The results confirm that a strong HR brand enhances organizational attractiveness, reduces staff turnover, and creates long-term competitive advantages. HR branding should be considered a comprehensive system that combines internal management practices with external communications, aligning business goals with employee expectations. Future research should focus on developing a next-generation HR branding model that integrates EVP, leadership culture, employee experience, technological maturity, inclusiveness, and ESG principles into a unified strategic architecture.